Peculiarities of changes in a functional condition of pro-oxidant and antioxidant systems in guinea pigs’ lungs in experimental allergic alveolitis under the conditions of immobilization stress - Baida, Mariana; Hot, Iryna; Antonenko, Yuliia (Journal of Education, Health and Sport, 2024)
We have analyzed the results of investigation of alterations in indices of pro-oxidant (conjugated diene and malondialdehyde) and antioxidant (superoxide dismutase, ceruloplasmin, catalase) systems in guinea pigs’ lungs in experimental allergic alveolitis in the dynamics of EAA development under the conditions of immobilization stress. The investigation was conducted on 62 female guinea pigs weighing 180-220 g, divided into 4 groups: I – intact guinea pigs (n=20), II – guinea pigs (n=14) with EAA under the conditions of IS (1st day); III – guinea pigs (n=14) with EAA under the conditions of IS (2nd day); IV – guinea pigs (n=14) with EAA under the conditions of IS (34th day). The results of experimental investigation showed that a significant increase in conjugated diene level in animals’ lungs was observed at all stages of EAA development under the conditions of immobilization stress as compared with control group, indicating activation of this marker. The same changes occurred with MDA content, indicating excessive accumulation of this lipid peroxidation product in lung tissue. Intensive synthesis of free radical compounds caused activation of some components of enzymatic system of antioxidant defense. In particular, a moderate decrease in superoxide dismutase activity in lung tissue is observed in response to increased level of LOPs at early stages of EAA and immobilization stress development as compared with the indices in intact animals. The same situation is observed with catalase and ceruloplasmin activity in the lungs of guinea pigs with modeled AA and IS.